The Relationship Between Interest Rates And Per Capita Income To Third Party Deposits (TPF) In Islamic Commercial Banks And Islamic Business Units In The Period 2010 - 2023 - Rahma Yuniarti P, Talitha (AL-ARBAH: Journal of Islamic Finance and Banking, 2025)
Purpose - This study was conducted to determine the effect of interest rates and per capita income on the amount of third party fund deposits in Islamic commercial banks and Islamic business units in the period 2010-2023. Method - There are 3 variables used to analyze the influence between variables in the short and long term using quantitative methods. Quantitative methods are used to conduct VECM analysis on variables obtained and processed from secondary statistical data found on the official website of the Financial Services Authority (OJK). Result - The results of the study indicate that the interest rate variable has a significant effect on the amount of Third Party Fund (DPK) deposits in the short term. Meanwhile, interest rates and per capita income simultaneously affect DPK deposits in BUS and UUS in the long term. Implication - This is in line with the statement of the Classical Theory regarding the interest rate level can affect the amount of deposits in banks. Originality - This paper examines the relationship between interest rates and per capita income on third party fund deposits in order to maintain liquidity and stability in BUS and UUS. Keywords:                     Interest Rate, Per Capita Income, DPK, Classical Theory, VECM.